Analisis Profil Konsumen Menggunakan Empathy Map Pada Startup Prove Fragrance - Dicky Hariyadi Erikson; Agus Maolana Hidayat (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In Indonesia, the cosmetics industry has experienced significant revenue growth in recent years, including in the perfume product category. One of the local brands that has emerged is Prove, but the company has experienced a recent decline in sales. Prove feels that the products they currently offer do not meet the desires and needs of the market segments they target. Despite establishing segmentation and targeting, in practice, this has not increased their sales. This research aims to identify the problems faced by Prove by analyzing their consumer profiles. The goal is for Prove to understand the desires and needs of consumers who constitute their market segments. The research method used is a descriptive qualitative approach. Data was collected through field observations and interviews with predetermined informants using purposive sampling method. This research utilizes Empathy Maps with several indicators such as seeing, hearing, thinking and feeling, saying and doing, customer pain, and customer gain. The research findings indicate that consumers generally observe sales and promotions of perfume products both online and offline, while Prove's products themselves are found in social media posts. Informants prefer the Sequoia variant due to its long-lasting aroma and simple yet elegant design. However, some consumers complain about the Aoife variant, which they find less fresh and with a short-lived scent. Before purchasing perfume, consumers tend to seek information first. Some risks they worry about include Prove products not being registered with the BPOM, products being damaged during shipping, and errors in delivery. Keywords: Cosmetic Industry, Customer Profile, Empathy Map, Perfume